LEXICAL DIFFICULTIES IN TEACHING ENGLISH TO PRIMARY STUDENTS AND WAYS TO OVERCOME THEM (Universal International Scientific Journal, 2026)
The article analyzes the main lexical difficulties encountered in teaching English vocabulary to primary school students - phonetic-graphic asymmetry, polysemy, collocational stability and semantic interference from the native language. The study shows that the cognitive capabilities of young students, limitations in working memory and difficulties in perceiving abstract words affect the formation of lexical competence. The effectiveness of multimodal semantization, visual-cognitive supports, thematic-associative dictionaries and differential repetition techniques is justified as ways to overcome the problem.
Keywords: primary education, English vocabulary, lexical difficulties, polysemy, semantic interference, collocation, cognitive development, visual support, repetition technique, communicative method.